SOCIAL PSYCHOLOGY OF SCIENCE: REVIEW AND DISCUSSION OF A NEW AREA OF RESEARCH - Íñiguez Rueda, Lupicinio; Pallí Monguilod, Cristina (Anales de Psicología / Annals of Psychology, 2002)
ocial studies of science and technology are one of the most important areas of research in social sciences. Psychology and social psychology are also contributing to his development. This paper analyse the social psychology’s contribution to the study of science reviewing 457 bibliographic references and offering a thematic classification organised in two big categories, mainstream social psychology of science and critical social psychology of science. In the first one the subjects are: normative character of the scientific activity, social influence processes, social comparison processes, values and believes systems, ethics in scientific research, and organisational and institutional context of scientific research. In the second one: the binomial science/ideology, and science as rhetoric and discursive practice. Finally, the paper offers a discussion about the general characteristics of the social psychology of science and about the possibilities of continuity of this particular area of research.